EFFECTIVE STRATEGIES FOR TEACHING VOCABULARY AND ENHANCING MEMORIZATION (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In today’s cutting-edge era, since knowing, learning and having good memory skills in terms of words are the inherent part of occupying every language, lots of ways are discovered in both teaching and improving memory skills of those who acquire language. Interestingly, not everyone is aware of these useful tactics and the main goal of this text is to give a little but the base of the most beneficial techniques in remembering and enhancing new words in every language. The activities that are going to be explained can be mostly used by teachers, tutors but not by students.